National Intellectual Capital And Its Impact On Economic Growth In Arab Region - محمود يوسف; قابقلي ابتهال; أسعد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research comes for in trying to state the reality of national intellectual capital in Arab region and determine its contribution in economic growth for selected Arab countries by using Gross Domestic Products (GDP) indicator during the period (2015-2019), since the national intellectual capital is the real capital and the main source of economic growth in knowledge economic era. The research uses mainly the analytical descriptive method by reviewing literatures deals with national intellectual capital and depending on the data offered by World Intellectual Property Organization (WIPO) through Global Innovation Index (GII) and studying the relationship between (GII) index and (GDP) as an indicator of economic growth and analyzing this relationship by using SPSS-V20 program. The research mainly concludes that, there is a positive correlation between national intellectual capital according to (GII) index and (GDP) as a result, where the (GII) index with its component is a good indicator for national intellectual capital elements. The statistical analysis demonstrates that the low level of national intellectual capital in selected Arab countries, since the countries still depend on tangible source and natural capital such as oil and gaze and natural resources in enhancing its economic growth levels.